Evaluation of the ecological and geochemical condition of geosystems of subregions of Northern Bukovyna. - Khodan, Halyna (Iasi, 2022)
The study assessed the ecological and geochemical state of geosystems of the subregions of Northern Bukovyna: Prut-Dniester, Prut-Siret, and Bukovynian Carpathians. In the Prut-Dniester interfluve, the ecological condition of rural geosystems can be assessed as moderately favorable and low-favorable. Bukovynian Subcarpathians, in the middle part of Northern Bukovyna, are distinguished by favorable ecological conditions for both human life and rural tourism. The predominance of the leaching soil water regime of geosystems (sufficient rainfall) and notable wooded areas contributed to the sanitation of these landscapes from various artificial pollutions. The Carpathian subregion is the most distinct and unusual in terms of geoecological evaluation. There is a more complex set of natural conditions (vertical differentiation of landscape complexes). Fluvial terrace landscape complexes (with a chain or mosaic-scattered settlements) have highly favorable ecological and geochemical conditions. This subregion is the most optimal regarding the recreational and tourist trend. Among the geoecological factors of its development, it is worth noting the high quality of groundwater (drinking water), which, despite the excess precipitation, is sufficiently saturated with biologically essential macro- and micronutrients and have mostly medium hardness (Ca + Mg) and mineralization.
Keywords: ecological-geochemical condition; geoecological evaluation; ecological-geochemical conditions; geoecological factor; subregion